Acute severe hepatitis outbreak in children: A perfect storm. What do we know, and what questions remain? - Matthews, Philippa C.; Campbell, Cori; Săndulescu, Oana; Matičič, Mojca; Ruta, Simona Maria; Rivero-Juárez, Antonio; van Welzen, Berend Joost; Tan, Boun Kim; Garcia, Federico; Gherlan, George Sebastian; Çınar, Güle; Hasanoğlu, İmran; et al. (Frontiers in Pharmacology, 2022)
During the first half of 2022, the World Health Organization (WHO) reported an outbreak of acute severe hepatitis of unknown aetiology (AS-Hep-UA) in children, following initial alerts from the UK where a cluster of cases was first observed in previously well children aged <6 years. Sporadic cases were then reported across Europe and worldwide, although in most countries incidence did not increase above the expected baseline. There were no consistent epidemiological links between cases, and microbiological investigations ruled out known infectious causes of hepatitis. In this review, we explore the evidence for the role of viral infection, superimposed on a specific host genetic background, as a trigger for liver pathology. This hypothesis is based on a high prevalence of Human Adenovirus (HAdV) 41F in affected children, together with metagenomic evidence of adeno-associated virus (AAV)-2, which is a putative trigger for an immune-mediated liver injury. Roles for superantigen-mediated pathology have also been explored, with a focus on the potential contribution of SARS-Cov-2 infection. Affected children also had a high frequency of the MHC allele HLA-DRB1*04:01, supporting an immunological predisposition, and may have been vulnerable to viral coinfections due to disruption in normal patterns of exposure and immunity as a result of population lockdowns during the COVID-19 pandemic. We discuss areas of ongoing uncertainty, and highlight the need for ongoing scrutiny to inform clinical and public health interventions for this outbreak and for others that may evolve in future.